A Randomized Trial of Behavioral Nudges Delivered Through Text Messages to Increase Influenza Vaccination Among Patients With an Upcoming Primary Care Visit - Patel, Mitesh S.; Milkman, Katherine L.; Gandhi, Linnea; Graci, Heather N.; Gromet, Dena; Ho, Hung; Kay, Joseph S.; Lee, Timothy W.; Rothschild, Jake; Akinola, Modupe; Beshears, John; Bogard, Jonathan E.; et al. (American journal of health promotion, 2023)
Purpose To evaluate if nudges delivered by text message prior to an upcoming primary care visit can increase influenza vaccination rates. Design Randomized, controlled trial. Setting Two health systems in the Northeastern US between September 2020 and March 2021. Subjects 74,811 adults. Interventions Patients in the 19 intervention arms received 1-2 text messages in the 3 days preceding their appointment that varied in their format, interactivity, and content. Measures Influenza vaccination. Analysis Intention-to-treat. Results Participants had a mean (SD) age of 50.7 (16.2) years; 55.8% (41,771) were female, 70.6% (52,826) were White, and 19.0% (14,222) were Black. Among the interventions, 5 of 19 (26.3%) had a significantly greater vaccination rate than control. On average, the 19 interventions increased vaccination relative to control by 1.8 percentage points or 6.1% (P = .005). The top performing text message described the vaccine to the patient as “reserved for you” and led to a 3.1 percentage point increase (95% CI, 1.3 to 4.9; P < .001) in vaccination relative to control. Three of the top five performing messages described the vaccine as “reserved for you.” None of the interventions performed worse than control. Conclusions Text messages encouraging vaccination and delivered prior to an upcoming appointment significantly increased influenza vaccination rates and could be a scalable approach to increase vaccination more broadly.